Геометричний аналіз Пуанкаре і Мельникова трансверсального розщеплення сепаратрисних многовидів повільно збурених нелінійних динамічних систем. I - Самойленко, А.М.; Тимчишин, О.Я.; Прикарпатський, А.К. (Український математичний журнал, 1993)
On the basis of Poineare - Melnikov geometric analysis, sufficient criteria of heteroclinic splitting of separatrix manifolds are studied for slowly perturbed nonlinear dynamical systems with a small parameter. An example of disappearance of adiabatic invariance i»s considered for a certain mechanic system on the plane.